Risk Categories in Halal Food Transportation: A Preliminary Findings - Teh Zaharah Yaacob; Fadilah Abd. Rahman; Harlina Suzana Jaafar (International Journal of Supply Chain Management, 2018)
Theissue of halal food hasattracted public attention and the Malaysias local authority especially on the issues of halal food status and the risk of contamination along the halal food supply chain. The risks of contamination will affect the halal food products safety and quality. Therefore, this study seeks to identify risk categories that lead to contamination risk of halal food products during the transportation, storage, and distribution process in halal food supply chain. Using a qualitative approach, an in-depth interview was carried out with the management committee from the halal certified logistics providers in Malaysia. The recorded interviews were transcribed, translated, coded, and reconciled. Atlas.ti software (version 7) assisted in data coding to identify themes and subthemes for this study. Thefindings suggested that delay risk, natural hazard, and operational risk are the category of risks that would affect the halal food products safety and quality and halal status during the transportation process. Similarly, technology adoption risk and halal integrity risk are also important risk factors towards the process of risk categorization in halal food transportation and distribution process.